Characteristics of a rapid, point‐of‐care lateral flow immunoassay for the diagnosis of sickle cell disease. Issue 2 (26th November 2015) - McGann, Patrick T.; Schaefer, Beverly A.; Paniagua, Mary; Howard, Thad A.; Ware, Russell E.
Abstract : Sickle cell disease (SCD) is a common and life‐threatening hematological disorder, affecting approximately 400, 000 newborns annually worldwide. Most SCD births occur in low‐resource countries, particularly in sub‐Saharan Africa, where limited access to accurate diagnostics results in early mortality. We evaluated a prototype immunoassay as a novel, rapid, and low‐cost point‐of‐care (POC) diagnostic device (Sickle SCAN™) designed to identify HbA, HbS, and HbC. A total of 139 blood samples were scored by three masked observers and compared to results using capillary zone electrophoresis. The sensitivity (98.3–100%) and specificity (92.5–100%) to detect the presence of HbA, HbS, and HbS were excellent. The test demonstrated 98.4% sensitivity and 98.6% specificity for the diagnosis of HbSS disease and 100% sensitivity and specificity for the diagnosis of HbSC disease. Most variant hemoglobins, including samples with high concentrations of HbF, did not interfere with the ability to detect HbS or HbC. Additionally, HbS and HbC were accurately detected at concentrations as low as 1–2%. Dried blood spot samples yielded clear positive bands, without loss of sensitivity or specificity, and devices stored at 37°C gave reliable results. These analyses indicate that the Sickle SCAN POC device is simple, rapid, and robust with high sensitivity and specificity for the detection of HbA, HbS, and HbC. The ability to obtain rapid and accurate results with both liquid blood and dried blood spots, including those with newborn high‐HbF phenotypes, suggests that this POC device is suitable for large‐scale screening and potentially for accurate diagnosis of SCD in limited resource settings. Am. J. Hematol. 91:205–210, 2016. © 2015 Wiley Periodicals, Inc.